An English-Hindustani Vocabulary - Phillott, D.C., (Brill | Manohar Publishers & Distributors, 2024)
Hindustani, also known as Hindi-Urdu, was one of the most popular languages during the eighteenth century. It is widely spoken in Northern India, Deccan, and parts of Pakistan. It retained its grammar and core vocabulary of the then-medieval Delhi province dialects with Persian, Arabic, and Turkic words. This language was developed as the result of linguistic diversity during the Muslim hegemony in India. Hindustani was further developed during the British era. Even, the father of the Indian nation, Mahatma Gandhi, also favoured Hindustani as the language of India. But today, it is generally associated with the language spoken by North Indian and Deccani Muslims. This book is a bilingual work, representing 5184 English words, and 3000 Hindustani colloquial words, and this list contains common words spoken on an everyday basis by the countryside population of Northern India.